Epizootiological. Study of sheep and goat abortion by Salmonella abortus ovis in Greece - GIANNATI-STEFANOU (Α. ΓΙΑΝΝΑΤΗ-ΣΤΕΦΑΝΟΥ) A.; BOURTZI-HATZOPOULOU (Ε. ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ) E.; SARRIS (Κ. ΣΑΡΡΗΣ) K.; XENOS (Γ. ΞΕΝΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The epizootiological data concerning sheep and goat abortion cases were studied between 1980-1989. The abortion cases were investigated by cultural or serological exaninations. From the affected flocks, where abortions took place, 1.69% to 19.35% were considered as infected by Salmonella abortus ovis SAO after isolation of the organism. The serological examinations of flocks with abortions, revealed a positivity to SAO of 2.7% to 47%. The infected sheep flocks, that were ascertained by isolation of SAO prevailed against the corrensponding goat herds with an average of 11.25% to 6% respectively.